Characterizing Cell Stress and GRP78 in Glioma to Enhance Tumor Treatment - Liu, Kristie; Tsung, Kathleen; Attenello, Frank J. (Frontiers in Oncology, 2020)
Glioblastoma (GBM) is the most common primary brain tumor, carrying a very poor prognosis, with median overall survival at about 12 to 15 months despite surgical resection, chemotherapy with temozolomide (TMZ), and radiation therapy. GBM recurs in the vast majority of patients, with recurrent tumors commonly displaying increase in resistance to standard of care chemotherapy, TMZ, as well as radiotherapy. One of the most commonly cited mechanisms of chemotherapeutic and radio-resistance occurs via the glucose-regulated protein 78 (GRP78), a well-studied mediator of the unfolded protein response (UPR), that has also demonstrated potential as a biomarker in GBM. Overexpression of GRP78 has been directly correlated with malignant tumor characteristics, including higher tumor grade, cellular proliferation, migration, invasion, poorer responses to TMZ and radiation therapy, and poorer patient outcomes. GRP78 expression is also higher in GBM tumor cells upon recurrence. Meanwhile, knockdown or suppression of GRP78 has been shown to sensitize cells to TMZ and radiation therapy. In light of these findings, various novel developing therapies are targeting GRP78 as monotherapies, combination therapies that enhance the effects of TMZ and radiation therapy, and as treatment delivery modalities. In this review, we delineate the mechanisms by which GRP78 has been noted to specifically modulate glioblastoma behavior and discuss current developing therapies involving GRP78 in GBM. While further research is necessary to translate these developing therapies into clinical settings, GRP78-based therapies hold promise in improving current standard-of-care GBM therapy and may ultimately lead to improved patient outcomes.